IFRS Compliance and Nonfinancial Information in Annual Reports of Malaysian Firms - Hla, Daw Tin; Md Isa, Abu Hassan bin; Shaikh, Junaid M. (EBSCOHOST, 2013)
This study analyzes the level of International Financial Reporting Standards (IFRS) compliance practice by the nonfinancial corporations from the different sectors, listed on the main market of Bursa Malaysia. It also analyzes the association between the level of IFRS compliance practice and nonfinancial information like early adoption of IFRS, good corporate governance practice, transparency and disclosure in their annual reports, etc. Research methodology includes content analysis to measure the level of IFRS compliance practice in annual reports of the firms, based on the measurement attributes of disclosure requirements of commonly used 14 IFRS. Multiple regression model estimates the instrumental nonfinancial variables that are accounted for the financial reporting with higher IFRS compliance practice by the firms in Malaysia. The findings highlight that financial reporting with the higher level of IFRS compliance in the annual reports is positively associated with nonfinancial factors like early adoption of IFRS, corporate governance, and transparency and disclosure practice. This study contributes to the evidence of higher IFRS compliance practice by the firms in Malaysia, and reveals the significant role of nonfinancial factors in achieving the mission of full convergence with IFRS in the internationalization of accounting in Malaysia.